Intellectual Capital and Islamicity Performance Index: Does it affect to Profitability of Islamic Commercial Banks? - Nur Hapsari, Adelia; Hasyim, Fuad (IAIN Kudus, 2023)
The financial performance of Islamic banking is not only measured through theassessment of financial entities such as financial ratios but also encompasses an evaluation of human capital. This research aims to assess the intellectual capital (IC) and Islamicity Performance Index (IPI) on the financial performance of Islamic Commercial Banks using profitability as a proxy. This study adopts a quantitative research approach using secondary data. The sample consists of 12 Islamic Commercial Banks selected through purposive sampling technique during the observation period from 2021 to 2022. The data analysis technique employed is regression analysis using a panel modeling approach. The findings indicate that Islamic Banking Value Added Capital Employed (iB-VACA), Islamic Banking Value Added Human Capital (iB-VAHU), Profit Sharing Ratio (PSR), and Equitable Distribution Ratio (EDR) have a significant influence on profitability. However, Islamic Banking Structural Capital Value Added (iB-STVA) does not have a significant impact on the profitability of Sharia commercial banks.Keyword : Profitability, IC, IPI, Panel